28-6x=49-9x

Simple and best practice solution for 28-6x=49-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 28-6x=49-9x equation:


Simplifying
28 + -6x = 49 + -9x

Solving
28 + -6x = 49 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
28 + -6x + 9x = 49 + -9x + 9x

Combine like terms: -6x + 9x = 3x
28 + 3x = 49 + -9x + 9x

Combine like terms: -9x + 9x = 0
28 + 3x = 49 + 0
28 + 3x = 49

Add '-28' to each side of the equation.
28 + -28 + 3x = 49 + -28

Combine like terms: 28 + -28 = 0
0 + 3x = 49 + -28
3x = 49 + -28

Combine like terms: 49 + -28 = 21
3x = 21

Divide each side by '3'.
x = 7

Simplifying
x = 7

See similar equations:

| (X+1)=x | | 14y+41=139 | | 0.33333333333(21-3a)=6-a | | 3x+2x-11=84 | | 6x+0.4=6.4 | | -2x-18=-(1-2x)+4x | | 4(a+2)=14-2(3-a) | | 4n=5-5n | | 88=12x-44 | | 16x-16-8x-12=3 | | 9-4b=4-3b-6b | | 16-(2x-3)=6 | | 6x-14=2(3x-72) | | 11x-13=5(2x+4)-7 | | 45=29-2(x-3) | | 2x^2-y^2-8x+6y-2=0 | | 8a+10=50 | | 7+7k=8k+2 | | -6m+3m=4-m | | 1000=20x+100y | | nsquared+n-105=0 | | 3a-6+7-2a= | | 0.19-0.03(x+1)=-0.02(2-x) | | 9y-187+x+44=180 | | -6n=-9 | | 4x-9x+12=2x+33 | | 8a-13=4a | | r+8=-4r-7 | | 140+0.40=50-0.70 | | 8x+16=-1 | | 25x+25=3(6x+6)+7x+7 | | 2x-7x+60=3x+36 |

Equations solver categories